DISONANSI NADA DALAM HARMONI MUSIK MEDITASI:: EKSPLORASI KONSEP ZEN BUDDHISM PADA KARYA DENGAN JUDUL “SATORI” - Abigail A., Kadek Ayu Neesha; Darmayuda, I Komang (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Music plays a central role in conveying messages and expressing emotions, often serving as an escape from daily life. In the context of Western music production, complexity is commonly considered a measure of the value of a musical work. However, this work aims to present a new perspective by asserting that beauty exists in simple music. Inspiration is drawn from meditation music, a discourse that fosters reflection and contemplation through the medium of music. Meditation music, as a means to seek tranquility and mental balance, can influence listeners physically, spiritually, and emotionally. This research explores the dissonance of tones within the harmony of meditation music, bringing forth new thoughts on musical elements and integrating principles of Zen Buddhism, particularly the concept of satori as the essence of Zen that reflects the teachings of enlightenment. The hope is that this composition not only enriches the auditory experience but also provides support in the journey of individuals seeking tranquility amidst the chaos of daily life.